2020
DOI: 10.1039/c9ta13932j
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Ln–MOF with tunable emission for heavy metal ion capture and l-cysteine sensing in serum

Abstract: Efficient turn-on luminescent probes for l-cysteine sensing in serum are designed and synthesized based on an anionic Ln–K–MOF with tunable emission color and heavy metal ion adsorption capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…Luminescent probes are considered to be ideal for detecting amino acids due to the advantages of simple operation, high sensitivity and selectivity. [38][39][40] In addition, acetylacetone (acac) is a toxic and volatile substance causing great harm to the human body and environment. 41,42 Therefore, efficient detection of acac has become the focus of environmental science.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent probes are considered to be ideal for detecting amino acids due to the advantages of simple operation, high sensitivity and selectivity. [38][39][40] In addition, acetylacetone (acac) is a toxic and volatile substance causing great harm to the human body and environment. 41,42 Therefore, efficient detection of acac has become the focus of environmental science.…”
Section: Introductionmentioning
confidence: 99%
“…Copper Ion (Cu 2+ ): The high concentration of Cu 2+ is harmful to human health, resulting in cancer, and organ damage. [73,74] In drinking water, a limited concentration of 0.05 mg L −1 has been permitted by the World Health Organization. Zhou and Wang et al reported a ratiometric luminescent RhB@ZIF-8, which was prepared through encapsulating dye molecule Rhodamine B (RhB) into ZIF-8.…”
Section: Heavy Metal Ionsmentioning
confidence: 99%
“…As a new kind of porous material, metal-organic frameworks (MOFs) have a wide application prospect in environmental monitoring, medical treatment, and industrial production. [1][2][3][4][5] The highly adjustable feature of MOFs endows them with flexibly control structure and composition by changing the metal centers and organic linkers. Therefore, the structural diversity, persistent porosity, as well as adjustable chemical and physical properties make various MOFs excellent sensors for detecting ions.…”
Section: Introductionmentioning
confidence: 99%